Calculation on the impact of a compensatory quota on consumers welfare: An illustrative case - Nuñez, Gaspar; Rodríguez, Ma. del Refugio; De la Cruz, Salvador (Estudios Económicos de El Colegio de México, 1996)
The most common approach used to evaluate changes in welfare has been the Consumer and Producer Surplus Analysis. This article presents a methodological alternative in order to evaluate in a more exact way this kind of modifications; in this sense, it includes some recent theoretical developments relating consumers welfare. By means of using the concept of Equivalent Variation and econometric and time series techniques, this work measures the impact of the implementation of antidumping duties on the imports of Chinese pommel locks in the Mexican consumers welfare.